2019
DOI: 10.1136/bjsports-2018-100087
|View full text |Cite
|
Sign up to set email alerts
|

How common is imaging for low back pain in primary and emergency care? Systematic review and meta-analysis of over 4 million imaging requests across 21 years

Abstract: word count: 304 Manuscript word count: 3392 2 ABSTRACT Objectives: To (i) estimate the proportion of patients seeking care for low back pain (LBP) who are imaged, and (ii) explore trends in the proportion of patients who received diagnostic imaging over time. We also examined the effect of study-level factors on estimates of imaging proportion. Eligibility criteria for selecting studies: Observational designs and controlled trials that reported imaging for patients presenting to primary care or emergency care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 86 publications
2
99
0
7
Order By: Relevance
“…At present, primary care decisionmaking for MSK pain is mostly based on ruling out serious pathology and using clinical reasoning without formal stratification tools to decide on treatment. Assessing the severity, impact and prognosis of individual patients can be difficult in short primary care consultations and patient access to other treatments is often variable [19][20][21][22]. Offering everyone consulting in primary care with MSK pain further treatments is both unnecessary and impractical [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…At present, primary care decisionmaking for MSK pain is mostly based on ruling out serious pathology and using clinical reasoning without formal stratification tools to decide on treatment. Assessing the severity, impact and prognosis of individual patients can be difficult in short primary care consultations and patient access to other treatments is often variable [19][20][21][22]. Offering everyone consulting in primary care with MSK pain further treatments is both unnecessary and impractical [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We found more than 880,000 routine diagnostic imaging procedures were performed between 2012-2016 during inpatient and outpatient care, with a ratio of approximate 10 images per 1000 individuals affected by LBP in Brazil. Inappropriate use of routine diagnostic imaging for LBP is being widely discussed [14,[42][43][44][45]. Previous studies demonstrated frequent referral for diagnostic imaging, despite the absence of red flags, such as infection, progressive neurologic deficits, or underlying pathologies [44,46].…”
Section: Discussionmentioning
confidence: 99%
“…However, current recommendations rather discourage imaging as part of early management of LBP, because of harms such as unnecessary exposition to radiation, patient fear and sense of fragility, and use of additional procedures resulting in overmedicalization [14,44]. Nonetheless, a systematic review [45] found a 53% relative increase in diagnostic imaging use (e.g., CT-scans) for LBP in primary and emergency care, from 1995 to 2015, despite guidelines advice and campaigns otherwise [47]. Clinicians and decision-makers should be aware that unnecessary diagnostic imaging wastes scarce financial resources [45,48], and has little effect on clinical outcomes [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations